Seasonal Dynamics of the Bacterial Community in Lake Urmia, a Hypersaline Ecosystem - Robab Salami; Abbas Saidi; Mohammad Amin Hejazi; Bahman Panahi; Rasmieh Hamid (Biology)
Lake Urmia is one of the world’s most unique and hypersaline aquatic ecosystems. The aim of this study was to investigate the diversity, abundance and frequency of these microorganisms in water samples from the eastern regions of the lake over four seasons. Amplicon sequencing for the 16S rRNA gene was performed to examine bacterial communities in the samples. The study revealed significant seasonal variations in water quality parameters and their influence on the microbial communities. Majority and rarity analyses showed that winter and spring had higher core abundance and higher Gini index values, indicating a greater dominance of certain genera, while autumn and summer had a more balanced distribution. Analysis of beta diversity using the Bray–Curtis dissimilarity index emphasized that bacterial communities diverge most strongly in summer and winter, reflecting the significant changes in the environment with the season. Overall, understanding the seasonal variation in water chemistry and bacterial communities is critical for effective ecosystem management and conservation efforts.